2022
DOI: 10.1111/gcb.16403
|View full text |Cite
|
Sign up to set email alerts
|

The global decline in the sensitivity of vegetation productivity to precipitation from 2001 to 2018

Abstract: The sensitivity of vegetation productivity to precipitation (S ppt ) is a key metric for understanding the variations in vegetation productivity under changing precipitation and predicting future changes in ecosystem functions. However, a comprehensive assessment of S ppt over all the global land is lacking. Here, we investigated spatial patterns and temporal changes of S ppt across the global land from 2001 to 2018 with multiple streams of satellite observations. We found consistent spatial patterns of S ppt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 60 publications
0
30
3
Order By: Relevance
“…However, our findings were not in line with the results of Zeng et al. (2022), who reported a global decline of vegetation‐water sensitivity during 2001–2018. Consequently, this increasing water limitation may imply a potential instability mechanism for ecosystems under climate change in the YRB.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our findings were not in line with the results of Zeng et al. (2022), who reported a global decline of vegetation‐water sensitivity during 2001–2018. Consequently, this increasing water limitation may imply a potential instability mechanism for ecosystems under climate change in the YRB.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study confirmed this phenomenon at the regional scale and highlighted the need for the conservation and efficient use of water resources in YRB. However, our findings were not in line with the results of Zeng et al (2022), who reported a global decline of vegetation-water sensitivity during 2001-2018. Consequently, this increasing water limitation may imply a potential instability mechanism for ecosystems under climate change in the YRB.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, regions with a significant negative correlation between SM and NDVI (P < 0.01) were labeled as "SM surplus" regions, where vegetation growth may be limited by energy-related factors. Recent reports (Denissen et al, 2022;Zeng et al, 2022;Y. Zhang et al, 2022) have indicated that the variations in the SM-NDVI interaction can be attributed to complex hydrometeorological changes during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Zeng et al. (2022) found that the global water‐vegetation interaction has declined during recent decades. Such uncertainties pose a challenge to our understanding of vegetation‐climate feedbacks.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation